Experimental determination of ZIP coefficients for residential appliances and ZIP model based appliance identification: The case of YTU Smart Home - Bircan, Mehmet; Durusu, Ali; Kekezoglu, Bedri; Elma, Onur; Selamogullari, Ugur Savas (ELSEVIER SCIENCE SA, 2020)
This study presents the experimental determination of the ZIP (constant impedance (Z), constant current (I), constant power (P)) coefficients for residential appliances in a smart home at Yildiz Technical University (the YTU Smart Home) in Istanbul, Turkey. First, active and reactive power consumptions of house appliances are measured with respect to the voltage change between 100-240 V with a 10 V increment. Then, Least Square Algorithm is used to calculate ZIP coefficients of household appliances. Using the obtained ZIP coefficients and an assumed appliance usage pattern, a daily residential active and reactive power demand profiles are obtained. Data from the ZIP models are compared with actual measurement data. It is shown that the ZIP models are quite accurate within 200-220 V voltage range and can be used in generating residential demand profiles for system level analyses. In addition, the ZIP model based appliance identification algorithm is proposed to identify the plugged appliance in the smart home environment for better home energy management algorithm implementation.
Keywords: Load model; Residential loads; ZIP coefficients; Appliance identification; Engineering